The habitus professorial and special education: perceptions of common class teachers and resource room multifuncional - Kuhn Junior, Norberto; Sardagna, Helena Venites; Pedde, Valdir; Roth, Fatima Liliane Oliveski (Faculdade de Ciências e Letras/Unesp, 2016)
This article analyzes the Inclusive Education from the Specialized Educational Service (SES) in Multifunctional Resources Classes (MRC) in the Municipal Teaching web in Novo Hamburgo/RS. It counted with the participation of 99 teachers in the regular classroom who worked as teachers of students with disabilities, pervasive developmental disorders, high ability/gifted and 30 MRC teachers in 2013. The data showed that the MRC teachers shown to have minor difficulties in working with students from the Special Education than the teachers of regular class. Through the identification of the teachers’ habitus of regular class, it was understood that the difficulties indicated by them derive from the fragility in their pedagogical training to work with students of Special Education. It is about a non-inclusive habitus, which is constituted from the internalization of teaching models based on the subject homogenization (all are equal) over the constitution of a new habitus, structural of a teaching model that recognizes the diversity for inclusion.